Structural, chemical and electrical characterization of organocyclotriphosphazene derivatives and their graphene-based composites - Koran, Kenan (Elsevier Science Bv, 2019)
In the present work, new di-spiro and tetra-spiro organophosphazene compounds (DPP-Ant-1 and 2, BPP-Ant-1 and 2) were synthesized by interaction with conjugate anthracene-substituted chalcone compounds (Ant-1 and 2) with organocyclotriphosphazene compounds DPP and BPP. All the compounds were fully characterized and confirmed by elemental analysis, spectroscopic and thermal techniques such as DSC, TGA, mass, FT-IR, H-1, C-13-APT, P-31 NMR and 2D HETCOR NMR. These organocyclotriphosphazes were designed and synthesized in order to investigate the changes in the conductive properties of graphene-based compounds. The graphene-based materials have a wide range of technological applications such as electronics, optics, thermal and mechanical properties. Graphene-based phosphazenes composites were prepared. The AC and DC conductivity of graphene-based phosphazene composites were measured. Dielectric measurements (dielectric constant, dielectric loss factors and conductivity) of organophosphazene compounds were measured against increasing frequency (range from 100 Hz to 20 kHz at 25 degrees C) at different temperature (between 298 and 348 K) using means of an impedance analyzer and then and compared with each other. Also, the activation energy profile of graphene/phosphazene composites was revealed by measuring DC conductivity of an individual composite material. The obtained graphene/phosphazene composites have been found that they have a semiconductor property according to the DC conductivity results. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Organophosphazene; Graphene-doped phosphazene; Electrical property; Graphene; Composites